The repressed trauma of a devoted English butler in The Remains of the Day by Kazuo Ishiguro - Yusoff, Siti Sarah; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2019)
Kazuo Ishiguro (b. 1954) is a Japanese diasporic writer residing in Britain and is a master of storytelling through his use of the melancholic and nostalgic elements to embody the fragmented self. In his 1989 Booker Prize winning novel, The remains of the day, Ishiguro portrays the main character, a butler named Stevens, who works under an aristocrat whom he highly respects which he later finds out had supported the Nazis during World War Two. The text is laden with Steven’s gradual acceptance of how his mentor eventually fails him and also how he denies himself of happiness in the pursuit of his career. Various studies from different perspectives have been conducted to examine the layers of complexity behind the characters and storytelling; for example, contesting how the stark scenery and setting changes in the novel reflect Steven’s state of mind through ecocriticism (Konlov, 2013) and a New Historicist reading to link how the storyline is parallel to real historical events regarding World War Two (Emara, 2015). Yet a much-overlooked aspect of the novel which needs to be addressed is the feeling of trauma felt by Stevens regarding his life with the aristocrat. Using the concept of trauma by Cathy Caruth, this study aims to analyse the novel focusing on the repressed memories of the protagonist, Stevens. Thus, the objective of the study is to examine how Stevens’ repressed memories as well as his British upbringing in shaping the experience he has undergone are reflected through the concept of trauma. The findings of the study demonstrate that indeed the trauma he has experienced is very much linked to the two elements.